HUMAN RIGHTS IN THE PERSPECTIVE OF THE COMPILATION OF ISLAMIC LAW - Dong, Muhammad (JSPH : Jurnal Sosial Politik Humaniora, 2024)
The aim of this research is to understand human rights from the perspective of a compilation of Islamic law. The compilation of Islamic law views that human rights are rights inherent in the human soul which are independent and cannot be taken away. The existence of huquq al-ibad is an implementation of human rights so that human life can be happy. The presence of a compilation of Islamic law on human rights is a principle that must be developed in marriage cases as a right that must be fulfilled. The articles contained in the compilation of Islamic law certainly indicate the existence of rights that must be fulfilled in order to fulfill human needs. Keywords: Human Rights, Perspective, Compilation, Law, Islam